ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEROAN TERBATAS MENGGUNAKAN PEMBAYARAN GAJI (PAYROLL) MELALUI BANK SYARIAH (STUDI PADA PERSEROAN TERBATAS DI JAKARTA) - Jayanti Tresna, Putri Dwi; Mursyidah, Azizah; Thantawi, Tubagus Rifqy (SAHID BANKING JOURNAL, 2023)
Payroll is a mass employee payroll system, the intensity of which is much needed by the company. The use of a payroll system can make it easier for companies to pay their employees. For the company, salary is a burden that must be incurred by the company to run a business so that the company needs a remuneration system to be able to streamline costs, but the results obtained by the company from employees are also maximal. The research method uses a quantitative approach with factor analysis techniques. Data collection techniques using a questionnaire technique. With quantitative methods, namely the data obtained in the form of numbers that can be calculated with regard to the problem under study. The price and promotion variables together have a positive and significant effect on payroll decisions through Islamic banks, while the service factor has no positive influence on payroll decisions. This is obtained from the t-count value of each variable and the results of the F test simultaneously have a positive and significant effect on the dependent variable, namely consumer decisions. The results that have been carried out by the author show that the dominant price and promotion factors affect payroll decisions through Islamic banks.